Aerobic exercise for Parkinson's disease: a systematic review and meta-analysis of randomized controlled trials. - Hai-Feng Shu; Tao Yang; Si-Xun Yu; Hai-Dong Huang; Ling-Li Jiang; Jian-Wen Gu; Yong-Qin Kuang (PLoS ONE, 2014)
Although some trials assessed the effectiveness of aerobic exercise for Parkinson's disease (PD), the role of aerobic exercise in the management of PD remained controversial.The purpose of this systematic review is to evaluate the evidence about whether aerobic exercise is effective for PD.Seven electronic databases, up to December 2013, were searched to identify relevant studies. Two reviewers independently extracted data and assessed methodological quality based on PEDro scale. Standardised mean difference (SMD) and 95% confidence intervals (CI) of random-effects model were calculated. And heterogeneity was assessed based on the I2 statistic.18 randomized controlled trials (RCTs) with 901 patients were eligible. The aggregated results suggested that aerobic exercise should show superior effects in improving motor actions (SMD, -0.57; 95% CI -0.94 to -0.19; p = 0.003), balance (SMD, 2.02; 95% CI 0.45 to 3.59; p = 0.01), and gait (SMD, 0.33; 95% CI 0.17 to 0.49; p<0.0001) in patients with PD, but not in quality of life (SMD, 0.11; 95% CI -0.23 to 0.46; p = 0.52). And there was no valid evidence on follow-up effects of aerobic exercise for PD.Aerobic exercise showed immediate beneficial effects in improving motor action, balance, and gait in patients with PD. However, given no evidence on follow-up effects, large-scale RCTs with long follow-up are warrant to confirm the current findings.